2015 International Conference on Pervasive Computing (ICPC) 2015
DOI: 10.1109/pervasive.2015.7087135
|View full text |Cite
|
Sign up to set email alerts
|

Low complexity modified constant Log-Map algorithm for radix-4 turbo decoder

Abstract: Turbo decoding for 3GPP-LTE wireless communication standard is most challenging task to reduce computational complexity. This paper presents 8-state trellis VHDL implementation of radix-2 and radix-4 form. In a practical system, the original MAP algorithm is too complex for implementation. All the branch metrics required for calculating LLR values are stored in a RAM. Max * function is implemented with correction factor to improve performance. The proposed, implemented algorithm is almost identical to max * fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…At the same time, we also propose the Nor-LUT-Log-MAP algorithm, which uses the Nor-Log-MAP algorithm to calculate forward-state and backward-state metrics as well as the LUT-Log-MAP algorithm to compute external information and posteriori information. As shown in Figure 9, the decoding performance of the Nor-LUT-Log-MAP algorithm is less than that of the LUT-Nor-Log-MAP algorithm, and it can be concluded that the forward-state and backward-state metric computation requires a better algorithm in the turbo decoding process [18]. In [10], Sun et al proposed FFU to compute the metrics of every state.…”
Section: The Siso Design Of the Turbo Decodermentioning
confidence: 99%
“…At the same time, we also propose the Nor-LUT-Log-MAP algorithm, which uses the Nor-Log-MAP algorithm to calculate forward-state and backward-state metrics as well as the LUT-Log-MAP algorithm to compute external information and posteriori information. As shown in Figure 9, the decoding performance of the Nor-LUT-Log-MAP algorithm is less than that of the LUT-Nor-Log-MAP algorithm, and it can be concluded that the forward-state and backward-state metric computation requires a better algorithm in the turbo decoding process [18]. In [10], Sun et al proposed FFU to compute the metrics of every state.…”
Section: The Siso Design Of the Turbo Decodermentioning
confidence: 99%